2021
DOI: 10.3390/jcm10235653
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anesthetic Technique on the Occurrence of Acute Kidney Injury after Spine Surgery: A Retrospective Cohort Study

Abstract: The effects of anesthetics on acute kidney injury (AKI) after spine surgery have not been evaluated fully. This study compared propofol-based total intravenous anesthesia (TIVA) and volatile anesthetics in the development of AKI after spine surgery. This retrospective study reviewed patients who underwent spine surgery between 2015 and 2019. A logistic regression analysis was performed to identify risk factors for AKI. Additionally, after propensity score matching, the incidence of AKI was compared between TIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the eld of orthopedic surgery, including joint replacement procedures such as total hip, knee, and shoulder joint surgeries, the incidence of AKI ranges from 1.8-8.2% [4,13]. For spinal surgeries, the reported incidence of AKI is between 1.6% and 3.9% [14][15][16], while in spinal surgeries for individuals aged 80 and above, it has been reported to be 0-2.7% [17,18]. Factors associated with the onset of AKI include preoperative factors such as chronic renal dysfunction, diabetes, hypertension, anemia, liver dysfunction, and muscle injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the eld of orthopedic surgery, including joint replacement procedures such as total hip, knee, and shoulder joint surgeries, the incidence of AKI ranges from 1.8-8.2% [4,13]. For spinal surgeries, the reported incidence of AKI is between 1.6% and 3.9% [14][15][16], while in spinal surgeries for individuals aged 80 and above, it has been reported to be 0-2.7% [17,18]. Factors associated with the onset of AKI include preoperative factors such as chronic renal dysfunction, diabetes, hypertension, anemia, liver dysfunction, and muscle injury.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with the onset of AKI include preoperative factors such as chronic renal dysfunction, diabetes, hypertension, anemia, liver dysfunction, and muscle injury. Intraoperative factors encompass surgical invasion, hypotension, renal ischemia, anesthetic agents, while postoperative factors include decreased circulating blood volume, decreased cardiac output, renal ischemia, medications such as NSAIDs and antibiotics, acute lung injury, and in ammatory reactions [3,4,15]. In this study, the extent to which the surgical invasiveness of MIS-PLIF/TLIF affects renal function was particularly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that even transient AKI increases the risk of mortality, hospital costs, and length of stay. 5 Degenerative spine disease is a leading cause of the loss of functional health status. Degenerative spine disease arises from a combination of micro-and macromechanical injuries, metabolic processes and risk factors such as age, sex, work environment, and genetics.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that even transient AKI increases the risk of mortality, hospital costs, and length of stay. 5…”
Section: Introductionmentioning
confidence: 99%
“…Various incidence rates of postoperative acute kidney injury (AKI) have been reported depending on the type of surgery and drugs administered [ 1 , 2 , 3 ]. When AKI occurs, it not only delays recovery and affects postoperative outcomes but also increases mortality [ 4 ]. Risk factors for AKI include male sex, old age, chronic renal disease, heart failure, diabetes, intraoperative bleeding, nutritional status, and hypotension [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%